2009
DOI: 10.1002/ejic.200900095
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective, High‐Yielding Synthesis of Alcohol‐Functionalized Diphosphanes Utilizing Asymmetric Control with a Chiral Auxiliary

Abstract: Enantiomerically pure, alcohol-functionalized diphosphane ligands carrying one phosphorus and three carbon stereogenic centers were generated from the Diels-Alder reactions of phosphane-functionalized terminal alkenols [3-(diphenylphosphanyl)but-3-en-1-ol and 2-(diphenylphosphanyl)prop-2-en-1-ol] with 3,4-dimethyl-1-phenyl-1H-phosphole. The reactions were promoted and controlled by the organoplatinum complex containing ortho-metalated (R)-[1-(dimethylamino)ethyl]naphthalene, and both cycloadditions showed exce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…It has been well established that the chloro ligand trans to the ortho-metalated aromatic carbon in R - 3a is inert to displacement by any incoming phosphorus donor atoms. , Treatment of complex R - 3a with aqueous silver perchlorate in dichloromethane gave the intermediate cationic perchlorate complex R - 4a in essentially quantitative yield (Scheme ). In routine synthesis, however, this highly reactive species is not isolated, and therefore upon removal of the silver chloride, the CH 3 CN/CH 2 Cl 2 (1:2) solution of R - 4a was subsequently treated with 1 equiv of diphenylphosphine at −78 °C for the second-stage hydrophosphination reaction to generate the 1,3-diphosphine products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been well established that the chloro ligand trans to the ortho-metalated aromatic carbon in R - 3a is inert to displacement by any incoming phosphorus donor atoms. , Treatment of complex R - 3a with aqueous silver perchlorate in dichloromethane gave the intermediate cationic perchlorate complex R - 4a in essentially quantitative yield (Scheme ). In routine synthesis, however, this highly reactive species is not isolated, and therefore upon removal of the silver chloride, the CH 3 CN/CH 2 Cl 2 (1:2) solution of R - 4a was subsequently treated with 1 equiv of diphenylphosphine at −78 °C for the second-stage hydrophosphination reaction to generate the 1,3-diphosphine products.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the metal complexes will be able to provide two or more coordination sites to synthesize chiral versions of bidentate diphosphine ligands, thus providing avenues for ligand activation and stereochemical control. Over the past few years, our group has established that organopalladium complexes containing ( R )- or ( S )-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary are good promoters for synthesis of various chiral phoshine ligands by means of asymmetric Diels−Alder reactions and hydrophosphination reactions. , Continuing our efforts in the development of new kinds of chiral diphosphines ligands utilizing these useful auxiliaries, we now describe a facile strategy to synthesize four monophosphine palladium complexes with aldehyde, ester- and keto-functionalities from acrolein, and their second-stage hydrophosphination reactions under mild conditions and in the absence of any protection that generate the corresponding novel chiral 1,3-diphosphine products.…”
Section: Introductionmentioning
confidence: 99%
“…We had previously reported that orthometalated [1-(dimethylamino)­ethyl]­naphthalene palladium­(II) complexes and platinum­(II) complexes can act as a chiral template that promotes various reactions, namely, [4+2] cycloaddition, hydrophosphination, hydroamination, and hydroarsination reactions. , These reactions can generate many useful P -stereogenic phosphines under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…It is conceivable that the presence of proper functional groups, for instance hydroxyl, amino, or ester, on these chiral phosphine frameworks can efficiently improve both reactivity and enantioselectivity in many reactions through the secondary interactions with the reacting substrates . Over the past few years, our group has successfully prepared a series of functionalized chiral phosphine ligands by means of asymmetric hydrophosphination and Diels−Alder reactions, promoted by the organopalladium complexes containing ( R )- or ( S )-(1-(dimethylamino)ethyl)naphthalene as the chiral auxiliary. , In the course of these series of studies, the use of stoichiometric amounts of palladium complex as reaction promoter offers practical advantages. (1) By means of coordination, it can protect the phosphine species from oxidation or racemization especially when it comes to the synthesis of P -stereogenic phosphine ligands.…”
Section: Introductionmentioning
confidence: 99%